Unveiling Charge Carrier Recombination, Extraction, and Hot‐Carrier Dynamics in Indium Incorporated Highly Efficient and Stable Perovskite Solar Cells - Chaocheng Zhou (Advanced Science, 2022)
Abstract Perovskite solar cells (PSCs) have been propelled into the limelight over the past decade due to the rapid‐growing power conversion efficiency (PCE). However, the internal defects and the interfacial energy level mismatch are detrimental to the device performance and stability. In this study, it is demonstrated that a small amount of indium (In3+) ions in mixed cation and halide perovskites can effectively passivate the defects, improve the energy‐level alignment, and reduce the exciton binding energy. Additionally, it is confirmed that In3+ ions can significantly elevate the initial carrier temperature, slow down the hot‐carrier cooling rate, and reduce the heat loss before carrier extraction. The device with 1.5% of incorporated In3+ achieves a PCE of 22.4% with a negligible hysteresis, which is significantly higher than that of undoped PSCs (20.3%). In addition, the unencapsulated PSCs achieve long‐term stability, which retain 85% of the original PCE after 3,000 h of aging in dry air. The obtained results demonstrate and promote the development of practical, highly efficient, and stable hot‐carrier‐enhanced PSCs.